Intervensi Non Farmakologi terhadap Stres dan Nyeri pada Anak dengan Gangguan Hematologi - Saragih, Betti Arisanti; Allenidekania, Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to identify the relationship between disaster knowledge and skills of Indonesian Adventist University students and family preparedness for facing disasters. This research method uses descriptive quantitative research with a survey method which will describe the relationship between knowledge and skills of Indonesian Adventist University students as many as 187 respondents. The results of this study show that in general, the subjects have a moderate to high level of knowledge. This is different from the subject's skill level which, when compared with disaster knowledge, is found to be at a lower level. In conclusion, there is a significant relationship between disaster knowledge and family preparedness as well as between students' disaster skills and family preparedness in facing disasters that can occur at any time. Keywords: Family Preparedness, Disaster Skills, Disaster Knowledge